The structure and magnetic properties in Dy3+ doped SmCrO3 ceramics. Issue 15 (15th October 2017) - Huang, S.; Su, K.P.; Wang, H.O.; Shi, L.R.; Huo, D.X.
Abstract: The Dy 3+ doped SmCrO3 polycrystalline ceramics are prepared by solid state method. The structure and magnetic properties are investigated. All samples show orthorhombic structure with space group Pnma . Three magnetic transitions are detected in Dy 3+ doped SmCrO3 samples, which arise from the Cr 3+ -Cr 3+ interactions and the spin reorientation of Cr 3+, respectively. Both field cooled (FC) and zero field cooled (ZFC) exchange bias (EB) effects are observed in the prepared Sm1- x Dy x CrO3 ( x = 0 − 0.5) samples below the spin reorientation temperature ( T SR ), and the EB field ( H EB ) increases dramatically below T SR . With the increase of the doping level, the H EB is depressed. Three anomalous variations of magnetic entropy change (Δ S M ) derived from the isothermal magnetization are observed, which are consistent with the magnetic transitions. Compared with the Δ S M after ZFC processes, the anomalous variations of Δ S M at ~25 K almost disappear after FC processes due to the enhanced unidirectional anisotropy, and no obvious influence is observed for the other two anomalous variations after FC processes.